Ergonomics and Library Professionals-A Case Study of the University of Kerala - Rajan Pillai, C. V.; Jayalatha, K. T. (Journal of Information and Knowledge, 2016)
This paper attempts to analyse the health problems among library professionals working with computers in the Kariavattom Campus of University of Kerala. The survey reveals that many of them are suffering from health problems like Cumulative Trauma Disorders and musculoskeletal disorders, loss of concentration, irritability and dizziness due to emotional fatigue, muscle pain, etc due to prolonged use of computers and unfavourable working environment. Only a small number of employees of the university are consulting the physician occasionally and the others are not trying to get proper treatment for the health problems. The paper concludes with suggestions for the improvement of equipment and working environment.